Infrastructure-driven Approach to Digital Transition .......... 215 - Dudzik, Sławomir; Kawka, Inga; Śliwa, Renata (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
An alternative perception of the possible impact of ICT disruptiveness of the economy is presented, one different from the one embedded in the literature highlighting the impact through “broad” capital, spillovers and “industrial innovation.” The Internet and its products and services carry, on the one hand, the drive for hyper-centralization, and on the other the drive for efficiency gains by facilitating the emergence of self-sustaining communities, fenced off by others by a belief in a common identity. Ignoring social and economic power becomes increasingly illegitimate under the pressure of the contemporary explosion of inequality and the resulting capacity of social movements. How, then, have the legislative political processes of the EU been established in recent years to increase the participation of social groups in economic processes, to be interpreted as wider openness of the channels for more distribution of income in societies? In terms of Internet connectivity, a specific area is the regulation relating to telecommunications infrastructure. Infrastructure forms the basis of product and service offerings in digital markets, further providing the foundation for the creation of social and economic infrastructure conditioning the inclusion of communities in a political (civic, identity) and economic (productivity) sense. The optics presented herein (being of a contributory nature) on how the digital connectivity market is crucial in determining power and legitimization, competitiveness and economic prosperity entails the perception of legal and political frameworks of the information and communication sector (ICT) as strategic for an economy to thrive and widely distribute wealth across societies. The contributory character of the chapter is based on the threefold axis of the analysis, encompassing political, legal and economic perspectives. The analysis is embedded in the review of the legal and political endeavors of the European Commission to grab the benefits of digital transformation in the economic and political interests of all EU citizens. The Digital Market Act is based on the conviction that regulation of big technology companies, being gatekeepers, leads the way toward more competition and choice, greater innovation, better quality and lower prices. The expected shift of power is from gatekeepers to startups and small businesses as well as users across the economy. The legal underpinning of the EU political endeavor is to equip the economic and social entities with a level playing field to compete, innovate, produce and be better off. For the processes to strengthen performant digital infrastructure, starting with reliable network connections, fast and secure connectivity is the pivotal element. Therefore, the core line of the Gigabit Infrastructure Act regulation is support for connectivity infrastructure establishment to build capacity, empower people and reinforce incentives to trade.